Perinatal Management and Outcomes of Pregnancy Following Sheehan Syndrome: A Case Report and Literature Review - Yongchi Zhan; Tingting Xu; Xiaodong Wang; Dandan Shi (Wolters Kluwer Health, 2021)
Abstract. Pregnancy is rare and difficult in Sheehan syndrome patients. With the help of assisted reproductive technology, the patients even with panhypopituitarism can get pregnant again. Moreover, women with hypopituitarism have increased risk of pregnancy complications. Here we report a patient who suffered acute and severe Sheehan syndrome with panhypopituitarism and central diabetes insipidus got pregnant again by in vitro fertilization and embryo transfer. A regular and careful antenatal care was given by the cooperation between obstetricians and endocrinologists. Finally, she delivered a healthy female baby at 37+6 weeks of gestation with Apgar scores of 10 and 10 at 1 and 5 minutes, respectively. The patient and her baby were doing well at postpartum follow-up. The related articles were also reviewed. This case report is aimed to help clinical practitioners to make better decisions on the management of Sheehan syndrome or other type of hypopituitarism during pregnancy.